Android-Based Intelligent Farmer Power Management System. Issue 4 (June 2019) - Song, Yao; Zhu, Kun
Abstract: Intelligent farmer power management system software is available for intelligent, small, single-user rural farmer systems. It is mainly used for real-time monitoring, data analysis and comprehensive coordinated control of solar energy, farm household consumption and energy storage units. The traditional farmer power management system is based on the Internet B/S structure and is developed using a standard J2EE platform. It requires an independent computer, software server, and database server to support operation and access. Based on the Android operating system, middleware and key applications, the intelligent farmer power management system software platform is based on the basic business of intelligent farmer power system consumption management, and solves the needs of farmers for real-time and historical data consumption. The easy-to-carry mobile phone smart terminal device overcomes the drawbacks that must be accessed by a computer, and can be conveniently and flexibly used for login, data access and remote control at any time, and is an important means for intelligent agriculture and intelligent farmer business promotion.